(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to demonstrate the importance of the role played by banking compliance in reducing the risks of electronic payment in order to ensure the success of the bank with regard to its compliance with the laws, regulations and regulations of the Central Bank of Iraq. electronic? In solving its problems, the research relied on the hypothesis of correlation and influence, where the first main correlation hypothesis was: There is no statistically significant correlation between the dimensions of banking compliance and the dimensions of electronic payment risks, and the second main simple effect hypothesis: There is no statistically significant effect of banking compliance in The dangers of electronic payment, and the researcher reached a set of conclusions, the most prominent of which were: The Central Bank of Iraq does not effectively demand the offending bank to remove the chairman of its board of directors or any members of the board, nor does it provide adequate security means for the systems or their design or completion. The Council has developed new standards at all levels from time to time according to various standards, approved to detect deviations and errors, and to address them immediately.